Molecular detection of vector-borne agents in ectoparasites and reptiles from Brazil - Mendoza-Roldan, Jairo Alfonso; Ribeiro, Stephany Rocha; Castilho-Onofrio, Valeria; Marcili, Arlei; Simonato, Bruna Borghi; Latrofa, Maria Stefania; Benelli, Giovanni; Otranto, Domenico; Barros-Battesti, Darci Moraes [UNESP] (Elsevier, 2021)
Trombidiformes and Mesostigmata mites, as well as Ixodida ticks, infest ectothermic tetrapods worldwide, potentially acting as vectors of bacteria, viruses and protozoa. The relationship among ectoparasites, transmitted pathogenic agents (e.g., Borrelia spp., Coxiella spp., Hepatozoon spp., and Rickettsia spp.) and ectothermic hosts has been scarcely investigated. This research focuses on a large collection of Brazilian herpetofauna screened for the presence of arthropod ectoparasites and vector-borne microbial agents. Reptiles (n = 121) and amphibians (n = 49) from various locations were infested by ectoparasites. Following genomic extraction, microbial agents were detected in 81 % of the Acari (i.e. n = 113 mites and n = 26 ticks). None of the mites, ticks and tissues from amphibians yielded positive results for any of the screened agents. Blood was collected from reptiles and processed through blood cytology and molecular analyses (n = 48). Of those, six snakes (12.5 %) showed intraerythrocytic alterations compatible with Hepatozoon spp. gamonts and Iridovirus inclusions. Hepatozoon spp. similar to Hepatozoon ayorgbor and Hepatozoon musa were molecularly identified from seven hosts, two mite and two tick species. Rickettsia spp. (e.g., Rickettsia amblyommatis, Rickettsia bellii-like, Rickettsia sp.) were detected molecularly from four mite species and Amblyomma rotundatum ticks. Phylogenetic analyses confirmed the molecular identification of the above-mentioned microbial agents of mites and ticks related to snakes and lizards. Overall, our findings highlighted that the Brazilian herpetofauna and its ectoparasites harbour potentially pathogenic agents, particularly from the northern and south-eastern regions. The detection of several species of spotted fever group Rickettsia pointed out the potential role of ectothermic hosts and related arthropod ectoparasites in the epidemiological cycle of these bacteria in Brazil.
Keywords: Hepatozoon spp.; Lizards; Mites; Rickettsia spp.; Snakes; Ticks; Vector-borne diseases